Dictionary as genre: By a proposal for categorization - Pereira, Renato Rodrigues; Nadin, Odair Luiz [UNESP] (Universidade Estadual de Maringa, 2019)
Depending on the typology of the dictionary: monolingual, bilingual, special language, specialized etc., we can find different and important information that contribute greatly with the consultant in his process of searching for knowledge. In general terms, dictionaries are lexical repertoires organized into more or less stable structures that allow us different types of consultation. Therefore, the knowledge of lexicographic structures usually results prerogative to all those who want to take advantage of the potential that the lexicographic repertoires have. Constituted by a series of components arranged in a global structure, they maintain a dialogical characteristic between their parts, being characterized as one of the different existing textual genres. Thence, understanding the dictionary as a genre allows us to take advantage of the linguistic and extralinguistic information registered in the work more efficiently. In this article, as we reflect on the dictionary as a textual genre, we are guided by the theoretical principles related to textual genres, and we also base ourselves on the theoretical-methodological foundations of Lexicography, since these enable the planning and elaboration of the most different types of works. In this way, we demonstrate the possibility and the pertinence in considering the dictionary as a textual genre and not only as a text support.
Dicionário enquanto gênero textual: Por uma proposta de categorização
Keywords: Dictionary; Genre; Lexicography